Nasal High Flow for Stable Patients with Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis. (2nd November 2019) - Bonnevie, Tristan; Elkins, Mark; Paumier, Clément; Medrinal, Clément; Combret, Yann; Patout, Maxime; Muir, Jean-François; Cuvelier, Antoine; Gravier, Francis-Edouard; Prieur, Guillaume
Abstract: There is a growing body of evidence supporting the use of nasal high flow (NHF) to treat acute respiratory failure, particularly in Chronic Obstructive Pulmonary Disease (COPD) patients. Conversely, there are sparse data evaluating its effects in stable COPD patients. We identified randomized controlled trial comparing the effects of delivering air or oxygen via NHF, compared with delivering the same gas without NHF, in stable COPD patients through a systematic search using MEDLINE, CENTRAL, Science Direct, and others sources until January 2019. Study selection, data extraction and assessment of the risk of bias (using the Cochrane Risk of Bias tool) was performed by two independent authors. We included 6 studies (339 participants). Our meta-analysis showed a significant reduction of arterial carbon dioxide pressure (PaCO2 ) at long (two studies, MD −3 mmHg, [95% Confidence interval (CI) −4 to −2]) and short-term (two studies, MD -3 mmHg [95% CI −4 to −2]). NHF significantly improved quality of life on the St George's Respiratory Questionnaire (two studies, MD −5 out of 100, [95% CI −8 to −2]). NHF significantly reduced the rate of acute exacerbation at 1 year (one study, rate ratio: 0.6, [95% CI 0.6 to 0.7]). NHF did not significantly improve exercise capacity, hospitalization rate or mortality, but improved breathing pattern. NHF reduced PaCO2, acute exacerbation and improved quality of life in stable COPD patients. Further long-term studies are needed to confirm the present results and provide more data on patient-centered outcome such as quality of life, exacerbation, hospitalization and mortality.